Implementation Of Musa's Leadership As A Role Model In The Field Of Teaching - Tony Tedjo; Witono Witono; Fandi Mulya Latif; Ary Setyowibowo (Eduvest - Journal of Universal Studies, 2024)
Leadership is always a topic of conversation for everyone, including in Christian circles. A good leader is a leader who has the ability to influence others to follow him. A good leader is also a leader who comes from God or a leader chosen by God. One of the leaders who is famous and widely recognized by the world is Moses, whose great leadership was recognized by four religions at once (Judaism, Christianity, Catholicism and Islam). Musa's leadership is one of the most influential leaderships in the world. Moses had implemented a good discipleship system. The discipleship system is a spiritual formation process that aims to improve a person's Christian faith and character. In the modern era, this discipleship system is increasingly important to face life's increasingly complex and diverse challenges. Without coaching and guidance from a church leader or fellow believer who is more spiritually mature, believers will experience stagnation in the growth of their faith. Without discipleship, believers may feel dissatisfied with the church and feel like they don't have a comfortable place to grow in their faith.